Application of Pontryagin’s Minimum Principle in Optimum Time of Missile Manoeuvring - Cahyaningtias, Sari; Subchan, Subchan (CAUCHY, 2016)
Missile is a guided weapon and designed to protect outermost island from a thread of other country. It, commonly, is used as self defense. This research presented surface-to-surface missile in final dive manoeuvre for fixed target. Furthermore, it was proposed manoeuvring based on unmanned aerial vehicle (UAV), autopilot system, which needs accuration and minimum both time and thrust of missile while attacking object. This paper introduced pontryagin’s Minimum Principle, which is useable to solve the problem. The numerical solution showed that trajectory of the missile is split it up in three sub-intervals; flight, climbing, and diving. The numerical simulation showed that the missile must climb in order to satisfy the final dive condition and the optimum time of a missile depend on initial condition of the altitude and the terminal velocity